2013
DOI: 10.5152/balkanmedj.2012.093
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Moderate and Strenuous Running on Trace Element Distribution in the Brain, Liver, and Spleen of Trained Rats

Abstract: Objective: Trace elements such as manganese (Mn), cobalt (Co) and chromium (Cr) play key roles in metabolic reactions and are important in many physiological enzymatic processes. In this study, we aimed to investigate the acute effects of moderate and strenuous running (treadmill) exercise on the levels of Mn, Co and Cr in the brain, liver, and spleen of trained rats.Study Design: Animal experiment.Material and Methods: Twenty-one Wistar-Albino adult male rats were used in the study. Rats were grouped as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…At the same time, no significant group difference was detected in other tissues including skeletal and cardiac muscle, liver, and hair . These data correspond to the study by Ergen et al (2013) who demonstrated that strenuous exercise resulted in a significant decrease in frontal lobe, liver, and spleen Co levels, whereas moderate exercise reduced metal levels in brain stem, liver, and spleen (Ergen et al, 2013). Hepatic Co levels were also reduced in rats exposed to strenuous swimming exercise (Sivrikaya et al, 2013).…”
Section: Cobalt Status In Athletessupporting
confidence: 89%
“…At the same time, no significant group difference was detected in other tissues including skeletal and cardiac muscle, liver, and hair . These data correspond to the study by Ergen et al (2013) who demonstrated that strenuous exercise resulted in a significant decrease in frontal lobe, liver, and spleen Co levels, whereas moderate exercise reduced metal levels in brain stem, liver, and spleen (Ergen et al, 2013). Hepatic Co levels were also reduced in rats exposed to strenuous swimming exercise (Sivrikaya et al, 2013).…”
Section: Cobalt Status In Athletessupporting
confidence: 89%
“…for 28 consecutive days. Higher Cr residues were detected in the brain homogenate tissues of the Cr-intoxicated group compared to the unexposed animals, indicating the ability of Cr to accumulate in the brain tissues and trigger neurotoxicity [ 41 ]. On the other hand, SA was shown to alter the biodistribution of Cr (VI) and reduce its levels in brain tissues, as evidenced by the notable reduction in the Cr level in the brain tissues of Group IV (Cr+SA) compared to the Cr-intoxicated group.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of chromium (VI) stress, a twofold increase in brain Mn levels accompanied increased Cr concentrations (75). Metabolic stress may alter Mn distribution in tissues, as suggested by a recent study that found decreased levels of Mn in the brain stem and frontal lobe after strenuous exercise relative to control conditions and moderate exercise (83). Dietary iron levels may have an impact on levels of Mn accumulation in the brain (96).…”
Section: Manganese Distribution and Concentrations In The Central Nermentioning
confidence: 99%